Polymer Conformation under Confinement - Bollas, Stavros (Polymers (Basel), 2017)
The conformation of polymer chains under confinement is investigated in intercalated polymer/layered silicate nanocomposites. Hydrophilic poly(ethylene oxide)/sodium montmorillonite, PEO/Na(+)-MMT, hybrids were prepared utilizing melt intercalation with compositions where the polymer chains are mostly within the ~1 nm galleries of the inorganic material. The polymer chains are completely amorphous in all compositions even at temperatures where the bulk polymer is highly crystalline. Attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR) is utilized to investigate the conformation of the polymer chains over a broad range of temperatures from below to much higher than the bulk polymer melting temperature. A systematic increase of the gauche conformation relatively to the trans is found with decreasing polymer content both for the C–C and the C–O bonds that exist along the PEO backbone indicating that the severe confinement and the proximity to the inorganic surfaces results in a more disordered state of the polymer.